Research Progress on Extraction and Separation of Active Components from Loquat Leaves - Siqiu Xiao; Wei Wang; Ying Liu (Separations, 2023)
Loquat is an evergreen tree belonging to the genus Loquat in Rosaceae. It is widely used in the processing of food and medicine. Based on the literature findings, the anti-tumor, antibacterial, anti-inflammatory and anti-oxidation activities of the extracted loquat leaves are related to its active components. The extracted loquat leaves, in addition, demonstrated remarkable, and privileged medicinal and commercial values, and recently attracted the interest of researchers. The current review aimed to summarize several important bioactive components in loquat leaves, their extraction and separation techniques, pharmacological activities, and research progress. In addition, the application prospect of bioactive components from loquat leaves was prospected, which provided a theoretical basis for its further development and utilization.